OPTIMISING THE ROLE OF POSYANDU HEALTH WORKERS IN INCREASING POSTNATAL VISITS TO POSYANDU - Okta Zenita Siti Fatimah; Seventina Nurul Hidayah (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
The postpartum period is a critical phase that requires regular maternal health monitoring to prevent complications such as bleeding and infection. However, data from the Tegal District Health Office in 2024 indicate that postpartum mothers’ attendance at posyandu remains relatively low, at only about 58%, which has not yet met the national target of 80%. This condition highlights the need for active involvement of posyandu cadres in improving postpartum visit rates. This study aims to identify the efforts made by posyandu cadres to increase postpartum mothers’ attendance at posyandu in Slawi Wetan Urban Village. The research employed a descriptive qualitative approach. Informants consisted of five posyandu cadres and four postpartum mothers who actively participated in posyandu activities. Data were collected through in-depth interviews and observation, then analyzed thematically. The results show that posyandu cadres undertook various efforts, including providing education on the importance of postpartum check-ups, conducting home visits, and reminding mothers of activity schedules through communication platforms such as WhatsApp. Supporting factors included assistance from health center staff and community enthusiasm, while challenges involved cadres’ limited time and low awareness among some postpartum mothers. In conclusion, posyandu cadres play an essential role in increasing postpartum visit rates through educational, persuasive, and personal approaches, although cross-sectoral support is still needed to achieve the expected target.